U.S. Multicenter Clinical Trial of Corneal Collagen Crosslinking for Treatment of Corneal Ectasia after Refractive Surgery - Hersh, Peter S.; Stulting, R. Doyle; Muller, David; Durrie, Daniel S.; Rajpal, Rajesh K.; Binder, Perry S.; Donnenfeld, Eric D.; Durrie, Daniel; Hardten, David; Hersh, Peter; Price, Francis; Randleman, J. Bradley; et al. (Ophthalmology (Rochester, Minn.), 2017)
To evaluate the safety and efficacy of corneal collagen crosslinking (CXL) for the treatment of corneal ectasia after laser refractive surgery. Prospective, randomized, multicenter, controlled clinical trial. One hundred seventy-nine subjects with corneal ectasia after previous refractive surgery. The treatment group underwent standard CXL, and the sham control group received riboflavin alone without removal of the epithelium. The primary efficacy criterion was the change over 1 year of topography-derived maximum keratometry (K), comparing treatment with control groups. Secondary outcomes evaluated were corrected distance visual acuity (CDVA), uncorrected distance visual acuity (UDVA), manifest refraction spherical equivalent, endothelial cell count, and adverse events. In the crosslinking treatment group, the maximum K value decreased by 0.7 diopters (D) from baseline to 1 year, whereas there was continued progression in the control group (1.3 D difference between treatment and control, P < 0.0001). In the treatment group, the maximum K value decreased by 2.0 D or more in 14 eyes (18%) and increased by 2.0 D or more in 3 eyes (4%). The CDVA improved by an average of 5.0 logarithm of the minimum angle of resolution (logMAR) letters. Twenty-three eyes (32%) gained and 3 eyes (4%) lost 10 or more logMAR letters. The UDVA improved 4.5 logMAR letters. Corneal haze was the most frequently reported crosslinking-related adverse finding. Corneal collagen crosslinking was effective in improving the maximum K value, CDVA, and UDVA in eyes with corneal ectasia 1 year after treatment, with an excellent safety profile. CXL is the first approved procedure to diminish progression of this ectatic corneal process.